Using machine vision to determine the rotational forces of electric motors - O.O. Shelukha; K.V. Molchanova; I.H. Babichev (Технічна інженерія)
The article considers the problem of measuring the torque of electric motors using machine vision technology. It is shown that traditional methods based on the installation of force-measuring sensors on the shaft of an electric motor require complex technological solutions and have limitations regarding the complexity of installation and operating costs. The article discusses the need for new methods of measuring the torque, and also shows the prospects of using machine vision technologies to solve this problem. A method of measuring the torque of electric motors is presented to improve the reliability of measurements, which can provide optimization in the maintenance of measurement systems.